Rational Choice Penjual Dan Pembeli Dalam Perdagangan Barang Counterfeit Di Pasar Taman Puring, Jakarta - Margaret, Monica; Sulung Esa, Alrizq Athallah (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2021)
The term counterfeit goods appears in the use of the brand field which refers to certain actions in seeking profit by trading, either producing or selling counterfeit, imitation or counterfeit goods. The labeling of counterfeit goods is taken from the way the goods are produced, namely by counterfeiting (forgery). This research is descriptive qualitative which explains the factors and causes behind sellers and buyers trading counterfeit goods which are analyzed with Rational Choice Theory which describes that criminals are seen as rational parties in making decisions and actions, as well as when buyers choose rational choice in buying counterfeit goods. In Indonesia, the business of counterfeit goods is growing in line with the lifestyle of the people in general. The research was conducted at Taman Puring Market, South Jakarta, which is the location of a large number of counterfeit goods trade. By obtaining data from several sources who are sellers and buyers of counterfeit goods, it is found that there are many factors that influence the occurrence of counterfeit goods trade, namely, price factors,quality factors, trend factors, needs factors, place reference factors and self-awareness factors. There are also many causes that can be measured from the point of view of Rational Choice Theory, namely profit, means, control and punishment.